THE PERMIAN -TRIASSIC BOUNDARY, DEAD SEA, JORDAN: TRANSITIONAL ALLUVIAL TO MARINE DEPOSITIONAL SEQUENCES AND BIOSTRATIGRAPHY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
The Permian to Triassic transition in Jordan is characterised by a sequence boundary underlain by red-bed, alluvial lithofacies deposited in a humid-tropical climate by low-sinuosity rivers, and overlain by shallow marine siliciclastics with thin carbonates. The low-gradient alluvial floodplain was repeatedly subjected to the development of ferralitic and pisolitic paleosols on the interfluves. In contrast, dysaerobic environments in the fluvial channels and abandoned lakes resulted in the preservation of a prolific flora of macro-plants and palynomorphs that indicate a probable range from Mid- to Late Permian age, though the abundant presence of the distinctive pollen Pretricolpipollenites bharadwajii  indicates the youngest part of that range.  Above the sequence boundary, reddened shallow-marine beds characterised by ripple cross-laminated, siltstones/sandstone with desiccation cracks and sparse surface burrows mark the initial Triassic marine transgression in the region (Arabian Plate Tr 10). These are followed by two thin limestone (packstone) beds with shallow scours and bivalve shell lags, that have yielded a low diversity assemblage of conodonts (e.g. Hadrodontina aequabilis) and foraminifera (“Cornuspira” mahajeri) that are interpreted as euryhaline  taxa characterising the early Induan (Early Triassic). Thus the absence of body fossils and vertical infaunal burrows in the lowest marine beds may reflect low-diversity ecosystems following the Permian-Triassic extinction event, or be a result of stressed shallow marine environments. A gradational upward increase in grey, green and yellow siltstones beds accompanied by a concomitant increase in bioturbation (and infaunal vertical burrows) and thin-shelled bivalves about 15 m above the boundary indicates colonisation of the substrate under more normal shallow marine conditions perhaps indicating recovery phase following the extinction event.